Thermodynamic properties of the first-order magnetic transition in the highly anisotropic 2D Blume-Capel model - Nguyen, Phong; Huong Giang, Bach (Communications in Physics, 2025)
The effect of anisotropy on the first-order magnetic transition (FOMT) in the highly anisotropic systems, such as perovskite manganite oxides, is investigated using Monte Carlo simulations of a two-dimensional (2D) spin \(S = 1\) Blume-Capel model with random anisotropy. For sufficiently large values of anisotropy probability \(p\) and corresponding amplitude \(D\), the second-order magnetic transition (SOMT) transforms into the FOMT. The presence of the FOMT is indicated not only by a sharp discontinuity in the magnetic moment at the critical temperature \(T_C^(1)\), but also by significant changes in the internal energy and magnetic moment histograms. As the type of the phase transition changes, thermodynamic observables display distinctly different behavior around \(T_C^(1)\). A phase diagram illustrating the SOMT-to-FOMT crossover induced by random anisotropy in high-\(p\) regimes is successfully constructed.